A Discrete Event System Approach to Online Testing of Speed Independent Circuits. (30th April 2015) - Biswal, P. K.; Mishra, K.; Biswas, S.; Kapoor, H. K.
Abstract : With the increase in soft failures in deep submicron ICs, online testing is becoming an integral part of design for testability. Some techniques for online testing of asynchronous circuits are proposed in the literature, which involves development of a checker that verifies the correctness of the protocol. This checker involves Mutex blocks making its area overhead quite high. In this paper, we have adapted the Theory of Fault Detection and Diagnosis available in the literature on Discrete Event Systems to online testing of speed independent asynchronous circuits. The scheme involves development of a state based model of the circuit, under normal and various stuck-at fault conditions, and finally designing state estimators termed as detectors. The detectors monitor the circuit online and determine whether it is functioning in normal/failure mode. The main advantages are nonintrusiveness and low area overheads compared to similar schemes reported in the literature.